KREDIBILITAS MUQĀTIL BIN SULAYMĀN DALAM PERIWAYATAN ISRĀ’ĪLIYYĀT - Fawaidur Ramdhani (STAI AL-ANWAR SARANG, 2020)
In the circle interpretation of the Quran, Muqātil Bin Sulaymān is not a unusual name. He was one of narrators of Isrā’īliyyāt from Tabi' al-Tabi'in. One of his works, Tafsir al-Kabīr, is constantly used as a representation of interpretations which are full of nuances of Isrā’īliyyāt. This tafsir is also famous as TafsirMuqātil bin Sulaymān. During his life, many negative accusations were addressed to him. This accusation caused the passiveness of Muslim scholars to examine Tafsir al-Kabīr. Despite the many negative accusations he received, Muqātil’s expertise in the field of Quranic study could not be doubted. Ahlu Hadith agree to dismiss every hadith narrated by Muqātil. However, in the caseof narration in the story of Isrā’īliyyāt, it seems that it prevailed the dismissal. This can be proven by the many interpretations that quote the narration of Muqātil. This article will discuss how Muqātil’s credibility in the narrative of the story of Isrā’īliyyāt. Will he be dismissed or vice versa.